2010
DOI: 10.1111/j.1524-4725.2010.01747.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Underdiagnosed Aggressive Non-Melanoma Skin Cancers Treated with Mohs Micrographic Surgery

Abstract: The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
2
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 6 publications
(12 reference statements)
3
43
2
7
Order By: Relevance
“…8 A more recent study showed a 51.1% accuracy rate between biopsy specimen and intraoperative examination of nonmelanoma skin cancers (BCC and squamous cell carcinoma). 10 A major and clinically important finding in our study is an overall 18% discordance rate between tumor subtype identification in the biopsy specimen and the composite BCC subtype. Sampling errors inherent in a small biopsy specimen of a large tumor would in part account for the observed discrepancy.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…8 A more recent study showed a 51.1% accuracy rate between biopsy specimen and intraoperative examination of nonmelanoma skin cancers (BCC and squamous cell carcinoma). 10 A major and clinically important finding in our study is an overall 18% discordance rate between tumor subtype identification in the biopsy specimen and the composite BCC subtype. Sampling errors inherent in a small biopsy specimen of a large tumor would in part account for the observed discrepancy.…”
Section: Discussionmentioning
confidence: 96%
“…Similar failure to detect aggressive tumor subtypes has also been reported in Mohs excision specimens where 21.1% of the cases examined intraoperatively revealed an aggressive subtype that was not diagnosed by biopsy specimen. 10 Another notable finding is that 19% of the discordant cases were misidentified as infiltrative BCC in the biopsy specimen as a result of surface ulceration and reactive stromal changes. In these cases, we observed that the biopsy specimen showed nodular BCC with ulceration and stromal reaction that could have altered tumor morphology and mimicked an infiltrative growth pattern.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Limited sampling during biopsy and pathology processing 6,7 fails to identify deeper and aggressive tumors in 1 of 6 cases, especially in mixed-histological subtypes 8,9 and in those superficial and nodular BCCs which have deeper components. 7,10 However, complete and accurate assessment of tumor subtype and depth is important for precise diagnosis and management, especially since skin cancer treatment guidelines list non-surgical options for the shallower and less-aggressive subtypes such as superficial and early nodular BCCs (depth ~0.2–0.5 mm) and surgical treatment for the aggressive and deeper subtypes such as micronodular, sclerosing and infiltrative. 3,4,11 Non-invasive optical imaging may help overcome these limitations and enable a more comprehensive assessment of lesions, and facilitate improved diagnosis, subtyping, and depth prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, another source of errors is the questionable reliability of the initial biopsy examination. The latter can in fact miss the more aggressive component of a composite BCC in more than 40% of cases [11,17,18]. Composite aggressive and non-aggressive BCCs have been detected in 38.5% of a series of 1,039 cases [11].…”
Section: Discussionmentioning
confidence: 99%